2000
DOI: 10.1038/35005132
|View full text |Cite
|
Sign up to set email alerts
|

The structure of malaria pigment β-haematin

Abstract: Despite the worldwide public health impact of malaria, neither the mechanism by which the Plasmodium parasite detoxifies and sequesters haem, nor the action of current antimalarial drugs is well understood. The haem groups released from the digestion of the haemoglobin of infected red blood cells are aggregated into an insoluble material called haemozoin or malaria pigment. Synthetic beta-haematin (FeIII-protoporphyrin-IX)2 is chemically, spectroscopically and crystallographically identical to haemozoin and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
835
1
9

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 815 publications
(883 citation statements)
references
References 28 publications
38
835
1
9
Order By: Relevance
“…Spectra were recorded at 298 K. Chemical shifts are referenced to external tetramethylsilane (TMS). Magnetic susceptibility measurements were made using the Evans method, 7 using the equation appropriate for a superconducting magnet; (1) where χ M is the molar susceptibility of the paramagnetic substance in cm 3 /mol, Δν is the chemical shift difference (in ppm) between a reference proton in the sample and that in a solution lacking the paramagnetic compound, c is the concentration of FPIX in mol/mL, and χ D is the diamagnetic susceptibility of heme (6.9 × 10 −4 cgs units). The corrections for the susceptibility of the solvent and the difference in densities of the solvent and the solution are ignored.…”
Section: Methodsmentioning
confidence: 99%
“…Spectra were recorded at 298 K. Chemical shifts are referenced to external tetramethylsilane (TMS). Magnetic susceptibility measurements were made using the Evans method, 7 using the equation appropriate for a superconducting magnet; (1) where χ M is the molar susceptibility of the paramagnetic substance in cm 3 /mol, Δν is the chemical shift difference (in ppm) between a reference proton in the sample and that in a solution lacking the paramagnetic compound, c is the concentration of FPIX in mol/mL, and χ D is the diamagnetic susceptibility of heme (6.9 × 10 −4 cgs units). The corrections for the susceptibility of the solvent and the difference in densities of the solvent and the solution are ignored.…”
Section: Methodsmentioning
confidence: 99%
“…A wealth of evidence indicates that the main mode of action of CQ and other quinoline-based drugs is the inhibition of heme aggregation and hemozoin formation [8][9][10]. Although the structure of hemozoin has been solved and shown to be identical to that of synthetic β-hematin [11], the details of the aggregation process are not well understood. There is now general agreement on the predominance of the heme aggregation inhibition mechanism for quinoline-based drugs, but other important effects that have been noted in relation to antimalarial activity include lipophilicity and changes in basicity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the underlying molecular mechanism of the quinolines is based on association of the drugs with Fe(III)-heme and heme polymer, i.e., noncovalent binding, which can interfere with the heme polymerization pathway [5][6][7]. The polymerized heme accumulates in the form of an insoluble, microcrystalline black-brown pigment called hemozoin or the ma-laria pigment, which is identical to synthetic ␤-hematin and is not a polymer as previously thought but a repeating array of coordinated dimers, bound through reciprocal iron(III)-carboxylate bonds to one of the propionic side chains of each porphyrin and held together in a crystalline matrix by hydrogen bonding interactions [8]. Because the polymerization pathway is unique to the malarial parasite, it offers an attractive target for the design of new antimalarials.…”
mentioning
confidence: 99%